Implementation of Social-Studies Teaching Materials Based on Flipbook for Student Learning of Po'o Elementary School - Fatima, Siti; Hasan, Hasan; Jamaludin, Jamaludin (PT. Riset Press International, 2025)
Education is factor main in progress a country, because through education , the state can print source Power quality human beings . This is in accordance with quote that says that